Students' Perceptions of Their Own Victimization: A Youth Voice Perspective. (2nd July 2016) - Corby, Emma-Kate; Campbell, Marilyn; Spears, Barbara; Slee, Phillip; Butler, Des; Kift, Sally
Abstract : This article investigates the perceptions of 156 students who were victims of both traditional and cyberbullying (117 female, 45 male), ages 10 to 17 years, as to which form of bullying was more hurtful. Overall, students perceived traditional victimization to be more hurtful than cyber victimization. Reasons identified in the data to explain the different perceptions of victims were categorized and found to relate to: the bully, the bystanders, the bullying incidents, the emotional impact on the victim, and the victim's ability to respond. The perceptions of these students challenge a number of suppositions presented in the literature that attempt to explain why cyberbullying is associated with more negative outcomes than traditional bullying. The implications for antibullying programs to address these issues are discussed.